Molecular Individual-Based Approach on Triatoma brasiliensis: Inferences on Triatomine Foci, Trypanosoma cruzi Natural Infection Prevalence, Parasite Diversity and Feeding Sources - Almeida, Carlos Eduardo [UNESP]; Faucher, Leslie; Lavina, Morgane; Costa, Jane; Harry, Myriam (Public Library of Science (PLoS), 2016)
We used an individual-based molecular multisource approach to assess the epidemiological importance of Triatoma brasiliensis collected in distinct sites and ecotopes in Rio Grande do Norte State, Brazil. In the semi-arid zones of Brazil, this blood sucking bug is the most important vector of Trypanosoma cruzi—the parasite that causes Chagas disease. First, cytochrome b (cytb) and microsatellite markers were used for inferences on the genetic structure of five populations (108 bugs). Second, we determined the natural T. cruzi infection prevalence and parasite diversity in 126 bugs by amplifying a mini-exon gene from triatomine gut contents. Third, we identified the natural feeding sources of 60 T. brasiliensis by using the blood meal content via vertebrate cytb analysis. Demographic inferences based on cytb variation indicated expansion events in some sylvatic and domiciliary populations. Microsatellite results indicated gene flow between sylvatic and anthropic (domiciliary and peridomiciliary) populations, which threatens vector control efforts because sylvatic population are uncontrollable. A high natural T. cruzi infection prevalence (52–71%) and two parasite lineages were found for the sylvatic foci, in which 68% of bugs had fed on Kerodon rupestris (Rodentia: Caviidae), highlighting it as a potential reservoir. For peridomiciliary bugs, Galea spixii (Rodentia: Caviidae) was the main mammal feeding source, which may reinforce previous concerns about the potential of this animal to link the sylvatic and domiciliary T. cruzi cycles.